Risk Factors for Anemia in the Event of Low Birth Weight (LBW) - Nurrohmah, Anjar; Indarwati, Indarwati; Rahmawatie, Diyah (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Background: The prevalence of LBW is still high in the world and also in Indonesia.   Karanganyar Regency Health Profile (2021) The IMR rate in Karanganyar Regency in 2021 is 8.3 per 1000 live births. If a pregnant woman experiences anemia, this will have an impact on the pregnancy process itself, both on the mother and the fetus. Various factors contribute to LBW. In general, these factors can be viewed from the mother's and baby's side, placental factors and environmental factors. Factors for LBW originating from babies include premature birth and delayed fetal growth. The factor of transporting nutrients and oxygen from mother to fetus is very important in the process of fetal growth and development in the womb. Among them are related to complications and illnesses experienced by the mother during pregnancy.   Method: Descriptive quantitation using the method of searching medical records for LBW babies. Results: the majority of respondents were aged 20-35 years (81%), the majority of respondents had secondary education (72%), the majority of mothers did not work (53%), a small proportion of mothers with LBW babies had anemia.